2017
DOI: 10.1152/ajpregu.00410.2016
|View full text |Cite
|
Sign up to set email alerts
|

ETBreceptor contribution to vascular dysfunction in postmenopausal women

Abstract: Endothelin-1 (ET-1) contributes to age-related endothelial dysfunction in men via the ET receptor. However, there are sex differences in the ET-1 system, and ET receptors are modulated by sex hormones. The purpose of this study was to test the hypothesis that ET receptors contribute to impaired vasodilatory function in postmenopausal women (PMW). We measured flow-mediated dilation (FMD) using ultrasound, and cutaneous nitric oxide-mediated vasodilation during local heating (42°C) via laser Doppler flowmetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 71 publications
6
45
0
Order By: Relevance
“…In order to examine the role of augmented ET B R function in this attenuated microvascular vasodilator response, we locally administered the ET B R-specific antagonist BQ-788 during assessments of pharmacologically (exogenous ACh) and physiologically (local heating of the skin) stimulated endothelium- and NO-dependent dilation. Consistent with previous reports of an endothelium-dependent vasodilator role of ET B R in healthy premenopausal women(35, 36, 43), we found that ET B R-inhibition attenuated endothelium-dependent dilation via reduced NO-dependent dilation in HC. However, we found that ET B R-inhibition increased endothelium-dependent dilation, independent of NO-dependent mechanisms, in PrEC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In order to examine the role of augmented ET B R function in this attenuated microvascular vasodilator response, we locally administered the ET B R-specific antagonist BQ-788 during assessments of pharmacologically (exogenous ACh) and physiologically (local heating of the skin) stimulated endothelium- and NO-dependent dilation. Consistent with previous reports of an endothelium-dependent vasodilator role of ET B R in healthy premenopausal women(35, 36, 43), we found that ET B R-inhibition attenuated endothelium-dependent dilation via reduced NO-dependent dilation in HC. However, we found that ET B R-inhibition increased endothelium-dependent dilation, independent of NO-dependent mechanisms, in PrEC.…”
Section: Discussionsupporting
confidence: 92%
“…Cutaneous vascular conductance was calculated (CVC = laser Doppler flux/mean arterial pressure) and normalized to a percentage of site-specific baseline (% base) for constriction and site-specific maximum (% max) for vasodilation as per standard normalization procedures(20, 41-43). In the local heating protocol, within-site NO-dependent dilation was calculated as the difference between the local heating plateau and the post-L-NAME plateau.…”
Section: Methodsmentioning
confidence: 99%
“…Under a normal physiological state, the ET B receptor is primarily expressed on vascular endothelial cells to mediate dilation. In pathological conditions, the ET B receptor is expressed in vascular smooth muscle to mediate the vasoconstriction reaction, during which the ET B receptor undergoes a process from absence to presence on vascular smooth muscle . However, the mechanism underlying the intracellular change remains unclear .…”
Section: Discussionmentioning
confidence: 99%
“…Webb et al found that short-term intracoronary administration of estradiol resulted in a significant decrease in coronary sinus concentrations of ET-1 in postmenopausal women with coronary artery disease [25]. A recent study has shown that ET B -mediated vasodilatory capacity is decreased in postmenopausal women, compared to young women (Figure 1)[26]. This interesting finding suggests that impaired ET B -mediated vasodilatory function may be responsible, at least in part, for endothelial dysfunction manifested after menopause [26].…”
Section: Et-1 In Postmenopausal Hypertensionmentioning
confidence: 99%